The Influence of Work Flexibility and Leadership on Work Engagement of Generation Z with Job Satisfaction as an Intervening Variable - Joesah, Nurzalinar; Latumahina, Jeffry; Armaniah, Henny (Journal of Economics and Business (JECOMBI), 2025)
This study aims to analyze how work flexibility and leadership affect Generation Z’s work engagement, both directly and indirectly through job satisfaction. The research employs a quantitative survey approach, collecting data from 97 Generation Z employees across various industries in Indonesia. The Partial Least Squares Structural Equation Modeling (PLS-SEM) technique was used for data analysis, with the sample size determined using Cochran’s formula. The findings indicate that work flexibility significantly enhances job satisfaction but does not directly impact work engagement. In contrast, leadership strongly influences both job satisfaction and work engagement. Furthermore, job satisfaction mediates the relationship between leadership and work engagement, while no significant mediation effect is found for work flexibility. These results highlight the critical role of leadership in fostering engagement among Generation Z  employees. Organizationsaiming to enhance workforce engagement should focus on supportive leadership approaches while also ensuring work flexibility to improve job satisfaction. The study provides practical insights for human resource management strategies and suggests further research to explore additional moderating factors that may influence these relationships.